PENINGKATAN KETERAMPILAN MENULIS SURAT RESMI MELALUI MODEL PROBLEM BASED LEARNING PADA SISWA KELAS V SDN SERAG KABUPATEN PONOROGO - Citra Suminar; Dwi Setyadi; Lulus Irawati (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2025)
This research serves to improve the official letter writing skills of fifth-grade students at SDN Serag, Pulung District, Ponorogo Regency, through the Problem Based Learning model. The research was conducted in two cycles using a qualitative approach. Data collection techniques included observation, interviews, written tests, and documentation. The data analysis technique applied in this research is qualitative data analysis. The results showed that the Problem Based Learning model was able to improve students' ability to write official letters. In the pre-action phase, mastery was only 12.5%, increasing to 63% in Cycle I, and reaching 82% in Cycle II, exceeding the 75% target. Problem Based Learning also proved to make learning more enjoyable, enhance critical thinking, collaboration, conceptual understanding, meticulousness, independence, and the relevance of material to real-world situations. Although challenges such as discussion dominance and lack of confidence existed, overall Problem Based Learning was very effective.